RANCANGAN KONTROL GERAKAN SAMPLE CHANGER BERBASIS USB PADA PERANGKAT RADIOIMMUNOASSAY-RIA IP8 - Joko Sumanto; Sukandar Sukandar; Abdul Jalil; Cukarya Cukarya (BATAN, 2012)
A DESIGN OF USB BASED SAMPLE CHANGER MOVEMENT CONTROLLER ON THE IP8 RADIOIMMUNOASSAY-RIA EQUIPMENT. A sample changer movement controller system for the IP8 RIA equipment has been designed. The Radioimmunoassay equipment is commonly used to determine hormone or vitamin concentrations using nuclear techniques. The Ip8 RIA equipment is designed for automatic measurements on multiple samples using one well-type NaI(Tl) detector through sample changer control. The control is performed using mechanical system and software-controlled electronic system. When the motor is turned on and the sample tube is above the detector tube, the mechanical system rotates 14,4 degrees to slide a sample tube, then moves down 7 cm to insert the sample tube into the detector tube, then removes it from the detector tube by moving up 7 cm, then repeat this sequence until the motor is turned off. The electronic system is designed to turn the motor off using limit switches when the sample is inside the detector, to allow counting to proceed, and to turn the motor on after counting is completed, to allow the mechanical system to replace the sample tube inside the detector with the next sample tube. The design of the sample movement controller is discussed in detail in this paper. The result of the design process are schematics and production-ready PCB layout. It is concluded that this design can be applied to improve the performance of the IP8 RIA equipment. Rancangan kontrol gerakan sample changer BERBASIS USB pada perangkat Radioimmunoassay-RIA IP8. Telah dilakukan rancangan sistem pengatur gerakan sample changer pada perangkat RIA IP8. Perangkat radioimmunoassay biasa digunakan untuk mengetahui kadar hormon atau vitamin menggunakan teknik nuklir. Perangkat RIA IP8 dirancang untuk mengukur sampel yang banyak secara automatis melalui pengaturan sampel changer dengan satu detektor NaI(Tl) tipe sumur. Pengaturan ini dilakukan dengan sistem mekanik dan sistem elektronik yang dikontrol melalui perangkat lunak. Cara kerja sistem mekanik adalah, jika posisi tabung sampel berada di atas dan motor dihidupkan, maka gerakannya memutar horisontal 14,4 derajat untuk menggeser tabung kemudian turun 7 cm untuk memasukkan tabung sampel ke dalam detektor, kemudian naik lagi 7 cm untuk mengeluarkan tabung sampel kemudian berulang memutar kembali sampai motor dimatikan. Pada sistem elektronik dirancang guna menghentikan motor melalui limit switch jika posisi sampel berada di bawah (di dalam detektor) untuk kemudian dicacah dan motor akan dihidupkan kembali secara software jika pencacahan telah selesai, sehingga sampel akan naik dan bergeser mengganti sampel berikutnya untuk dicacah. Rancangan kontrol gerakan sampel tersebut dibahas secara detail pada makalah ini. Hasil rancangan modul ini berupa gambar skematik dan gambar PCB yang siap dicetak. Disimpulkan bahwa hasil rancangan ini dapat diterapkan untuk memperbaiki kinerja perangkat RIA IP8.